Promises of 1968 : crisis, illusion, and utopia - Tismaneanu, Vladimir (Central European University Press, 2011)
This book is a state of the art reassessment of the significance and consequences of the events associated with the year 1968 in Europe and in North America. Since 1998, there hasn't been any collective, comparative and interdisciplinary effort to discuss 1968 in the light of both contemporary headways of scholarship and new evidence on this historical period. A significant departure from earlier approaches lies in the fact that the manuscript is constructed in unitary fashion, as it goes beyond the East-West divide, trying to identify the common features of the sixties. The latter are analyzed as simultaneously global and local developments. The main problems addressed by the contributors of this volume are: the sixties as a generational clash; the redefinition of the political as a consequence of the ideological challenges posed to the statusquo by the sixtyeighters; the role of Utopia and the deradicalization of intellectuals; the challenges to imperialism (Soviet/American); the cultural revolution of the sixties; the crisis of 'really existing socialism' and the failure of "socialism with a human face"; the gradual departure from the Yaltasystem; the development of a culture of human rights and the project of a global civil society; the situation of 1968 within the general evolution of European history (esp. the relationship of 1968 with 1989). In contrast to existing books, the book provides a fundamental and unique synthesis of approaches on 1968: first, it contains critical (vs. nostalgic) reevaluations of the events from the part of significant sixtyeighters; second, it includes historical analyses based on new archival research; third, it gathers important theoretical reassessments of the intellectual history of the 1968; and fourth, it bridges 1968 with its aftermath and its prehistory, thus avoiding an overcontextualization of the topics in question